Features of teaching thermal injury course for the third-year students at the general surgery department. - V. Nagaichuk; M. Zheliba; R. Chornopyshchuk (Medičnì Perspektivi)
In the article, on the basis of methodological recommendations on the introduction of the European credit transfer system and its documents, current issues of optimizing the educational process, the effectiveness of mastering the material on the topic "Thermal trauma", based on theoretical training and practical skills are elucidated. Lectures, practical classes and skills are formulated taking into account modern terrorist attacks with outlining effective ways of medical self-aid, mutual and first aid.